Validating a six-pillar framework for restaurant entrepreneurship: Evidence from Thailand’s dynamic food sector - Pislae-Ngam, Kattakamon; Thammarakkitanon, Vipaspon (Edelweiss Applied Science and Technology, 2026)
The restaurant sector in Thailand is an integral part of its national economy and cultural identity, but the entrepreneurial competencies needed to succeed in it are a topic of considerable debate. This study develops and validates a comprehensive framework to fill this knowledge gap. A first-order confirmatory factor analysis (CFA) of survey data from 400 restaurant entrepreneurs across Thailand was used to validate a six-component model. The six validated components of entrepreneurial competencies were: Inspiration/Motivation (IPR), Proactiveness (PAT), Risk-Taking (RTK), Innovation (INV), Service Quality (SVQ), and Business Ethics (ETC). The study found that SVQ was the most important component, suggesting that this is a key entrepreneurial competence in this service-reliant industry. The model fit indices demonstrated that the measurement model had an excellent fit (CFI=0.95, RMSEA=0.01). The reliability and validity levels for all the constructs satisfied the thresholds. The validated framework provides a practical diagnostic tool for strengthening SME performance in Thailand’s restaurant sector.